Gravity-induced coronal plane joint moments in adolescent idiopathic scoliosis. Issue 1 (December 2015) - Keenan, Bethany; Pettet, Graeme; Izatt, Maree; Askin, Geoffrey; Labrom, Robert; Pearcy, Mark; Adam, Clayton
Abstract Background Adolescent Idiopathic Scoliosis is the most common type of spinal deformity, and whilst the isk of progression appears to be biomechanically mediated (larger deformities are more likely to progress), the detailed biomechanical mechanisms driving progression are not well understood. Gravitational forces in the upright position are the primary sustained loads experienced by the spine. In scoliosis they are asymmetrical, generating moments about the spinal joints which may promote asymmetrical growth and deformity progression. Using 3D imaging modalities to estimate segmental torso masses allows the gravitational loading on the scoliotic spine to be determined. The resulting distribution of joint moments aids understanding of the mechanics of scoliosis progression. Methods Existing low-dose CT scans were used to estimate torso segment masses and joint moments for 20 female scoliosis patients. Intervertebral joint moments at each vertebral level were found by summing the moments of each of the torso segment masses above the required joint. Results The patients' mean age was 15.3 years (SD 2.3; range 11.9–22.3 years); mean thoracic major Cobb angle 52° (SD 5.9° ; range 42–63° ) and mean weight 57.5 kg (SD 11.5 kg; range 41–84.7 kg). Joint moments of up to 7 Nm were estimated at the apical level. No significant correlation was found between the patients' major Cobb angles and apical joint moments. Conclusions Patients with larger Cobb angles do not necessarily have higher joint moments, and curve shape is an important determinant of joint moment distribution. These findings may help to explain the variations in progression between individual patients. This study suggests that substantial corrective forces are required of either internal instrumentation or orthoses to effectively counter the gravity-induced moments acting to deform the spinal joints of idiopathic scoliosis patients.